Canakinumab and Lung Cancer: Intriguing, but Is It Real? - Chabner, Bruce A. (Oncologist, 2018)
The relationship between inflammation and cancer is complicated. This editorial calls attention to intriguing findings of the CANTOS trial, which was designed to test the hypothesis that an anti‐inflammatory intervention could reduce the incidence of heart attacks, stroke, or cardiovascular death in patients with elevated C‐reactive protein.